Pembuatan Sistem Informasi KWT Mekar Lestari Desa Tengin Baru Guna Meningkatkan Penjualan - Fadila, Alda Ela; Hadiyanto, Hadiyanto (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
In Mekar Lestari's Women Farmers Group (KWT), there are many things that need to be developed. One of them is an activity and sales information system that still does not have a place to accommodate it. Lack of a platform to improve their information systems and sales of their crops. Therefore this information system is designed to help make it easier for women farmer groups to increase their sales and be able to publish activities and information about agriculture. The information system for the Mekar Lestari Women Farmers Group (KWT) in Tengin Baru Village aims to increase crop yields. This information system is like a web-based e- commerce. In the process of making this information system, the author uses MySQL as the database and uses PHP as the programming language. In addition, this information system is also used to help the women's farmer group Mekar Lestari to disseminate information and introduce activities in Sepaku so that it can develop and be known in various levels of society.